2009
DOI: 10.1007/s10856-009-3773-6
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and pharmaceutical/pharmacodynamic evaluation of topical brucine-loaded liposomal hydrogel

Abstract: To reduce the toxicity and enhance the therapeutic efficacy of brucine, a traditional Chinese medicine for relieving arthritic and traumatic pain, in this study, a novel brucine-loaded liposomal hydrogel (BLH) formulation, suitable for topical application, was developed. Spherical liposomes composed of lecithin and cholesterol, with brucine, was prepared by a modified ethanol-dripping method. High percentage (over 80%) of encapsulated brucine in liposomes was obtained. Topical liposomal hydrogel formulations w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…The hydrogel was prepared according to the previous paper with minor modification (Wang et al, 2009). Carbopol-940 powders (1 g) was weighted and added slowly into glycerin (8 g) under constant stirring by a glass rod.…”
Section: Preparation Of Hydrogelmentioning
confidence: 99%
See 2 more Smart Citations
“…The hydrogel was prepared according to the previous paper with minor modification (Wang et al, 2009). Carbopol-940 powders (1 g) was weighted and added slowly into glycerin (8 g) under constant stirring by a glass rod.…”
Section: Preparation Of Hydrogelmentioning
confidence: 99%
“…The amount of brucine in the skin was determined according to the previously reported method (Wang et al, 2009). After skin permeation experiment, the residual formulation on skin was cleaned by physiological saline solution, and then was wiped dry.…”
Section: In Vitro Skin Permeationmentioning
confidence: 99%
See 1 more Smart Citation
“…Vesicular gel formulations have been shown to affect percutaneous penetration for a number of substances, e.g. lipophilic substances, alkaloids and local anaesthetics [18–20] …”
Section: Introductionmentioning
confidence: 99%
“…lipophilic substances, alkaloids and local anaesthetics. [18][19][20] The skin is an effective barrier against xenobiotics and the stratum corneum is often described with the brick-and-mortar model. [21] It was suggested that the lipids of traditional vesicles may penetrate the skin's intracellular lipid layer and modify these lamellae.…”
Section: Introductionmentioning
confidence: 99%